Analgesia in the surgical intensive care unit. Issue 1095 (24th October 2016) - Ehieli, Eric; Yalamuri, Suraj; Brudney, Charles S; Pyati, Srinivas
ABSTRACT: Critically ill patients are a heterogeneous group with diverse comorbidities and physiological derangements. The management of pain in the critically ill population is emerging as a standard of care in the intensive care unit (ICU). Pain control of critically ill patients in the ICU presents numerous challenges to intensivists. Inconsistencies in pain assessment, analgesic prescription and variation in monitoring sedation and analgesia result in suboptimal pain management. Inadequate pain control can have deleterious effects on several organ systems in critically ill patients. Therefore, it becomes incumbent on physicians and nurses caring for these patients to carefully evaluate their practice on pain management and adopt an optimal pain management strategy that includes a reduction in noxious stimuli, adequate analgesia and promoting education regarding sedation and analgesia to the ICU staff. Mechanistic approaches and multimodal analgesic techniques have been clearly demonstrated to be the most effective pain management strategy to improve outcomes. For example, recent evidence suggests that the use of short acting analgesics and analgesic adjuncts for sedation is superior to hypnotic based sedation in intubated patients. This review will address analgesia in the ICU, including opioid therapy, adjuncts, regional anaesthesia and non-pharmacological options that can provide a multimodal approach to treating pain.